TURP syndrome and severe hyponatremia under general anaesthesia - Demirel, Ismail; Ozer, Ayse B.; Bayar, Mustafa K.; Erhan, Omer L. (BMJ Publishing Group, 2012)
Transurethral resection of prostate (TURP) syndrome is a complication characterised by symptoms changing from an asymptomatic hyponatremic state to convulsions, coma and death due to absorption of irrigation fluid during TURP. The syndrome appears to be related to the amount of fluid that enters the circulation via the blood vessels in the resection area. The first step in the course of action for therapy is to control bleeding and suspend the operation. In the case presented, we aimed to emphasise the importance of an early diagnosis and treatment of TURP syndrome in a patient that developed hyponatremia (90 mmol/l) while under general anaesthesia during a TURP procedure. In addition, multiple cystoscopic applications in the same session may facilitate development of the TURP syndrome. Copyright 2012 BMJ Publishing Group. All rights reserved.
Keywords: adrenalin; aminophylline; atropine; bicarbonate; ephedrine; furosemide; glyceryl trinitrate; methylprednisolone; noradrenalin; sodium; sodium chloride; aged; article; bladder stone; bradycardia; bronchospasm; case report; central venous pressure; continuous infusion; cyanosis; early diagnosis; general anesthesia; human; hypertension; hypervolemia; hyponatremia; hypotension; intraoperative period; lithotripsy; male; metabolic acidosis; priority journal; prostate hypertrophy; transurethral resection; transurethral resection syndrome; treatment outcome